Precambrian Paleobiology: Precedents, Progress, and Prospects - Schopf, J. William (Frontiers in Ecology and Evolution, 2021)
In 1859, C.R. Darwin highlighted the “inexplicable” absence of evidence of life prior to the beginning of the Cambrian. Given this lack of evidence and the natural rather than theological unfolding of life’s development Darwin espoused, over the following 50 years his newly minted theory was disputed. At the turn of the 19th century, beginning with the discoveries of C.D. Walcott, glimmerings of the previously “unknown and unknowable” early fossil record came to light – but Walcott’s Precambrian finds were also discounted. It was not until the breakthrough advances of the 1950’s and the identification of modern stromatolites (1956), Precambrian phytoplankton in shales (1950’s), stromatolitic microbes in cherts (1953), and terminal-Precambrian soft-bodied animal fossils (1950’s) that the field was placed on firm footing. Over the following half-century, the development and application of new analytical techniques coupled with the groundbreaking contributions of the Precambrian Paleobiology Research Group spurred the field to its international and distinctly interdisciplinary status. Significant progress has been made worldwide. Among these advances, the known fossil record has been extended sevenfold (from 0.5 to 3.5 Ga); the fossil record has been shown consistent with rRNA phylogenies (adding credence to both); and the timing and evolutionary significance of an increase of environmental oxygen ( 2.3 Ga), of eukaryotic organisms ( 2.0 Ga), and of evolution-speeding and biota-diversifying eukaryotic sexual reproduction ( 1.0 Ga) have been identified. Nevertheless, much remains to be learned. Such major unsolved problems include the absence of definitive evidence of the widely assumed life-generating “primordial soup”; the timing of the origin of oxygenic photosynthesis; the veracity of postulated changes in global photic-zone temperature from 3.5 Ga to the present; the bases of the advent of eukaryotic sexuality-requiring gametogenesis and syngamy; and the timing of origin and affinities of the small soft-bodied precursors of the Ediacaran Fauna.